Ectopic expression of AtNF-YA6-VP16 in petals results in a novel petal phenotype in Torenia fournieri - Sekiguchi, Natsumi; Sasaki, Katsutomo; Oshima, Yoshimi; Mitsuda, Nobutaka (Planta, 2022)
Main conclusion A novel Torenia phenotype having separate petals was obtained by the combination of NF-YA6 - VP16 with a floral organ-specific promoter. Genetic engineering techniques helped in obtaining novel flower colors and shapes, in particular, by introducing functionally modified transcription factors (TFs) to ornamental flower species. Herein, we used functionally modified Arabidopsis TFs fused with the repression domain SRDX and the activation domain VP16 to screen for novel floral traits in Torenia fournieri Lind (torenia). We avoided undesired phenotypes unrelated to flowers by expressing these TFs through a floral organ-specific promoter belonging to the class-B genes, GLOBOSA ( TfGLO ). Fourteen constructs were produced to express functionally modified Arabidopsis TFs in which each of SRDX and VP16 was fused into 7 TFs that were used for the collective transformation of Torenia plants. Among the obtained transgenic plants, phenotypes with novel floral traits reflected in separate petals within normally gamopetalous flower lines. Sequencing analysis revealed that the transgenic plants contained nuclear factor-YA6 ( NF-YA6 ) fused with the VP16 . In the margin between the lips of the petals and tube in the TfGLO p: NF-YA6 - VP16 plants, staminoid organs have been developed to separate petals. In the petals of the TfGLO p: NF-YA6 - VP16 plants, the expression of a Torenia class C gene, PLENA ( TfPLE ), was found to be ectopically increased. Moreover, expression of TfPLE-VP16 under the control of the TfGLO promoter brought a similar staminoid phenotype observed in the TfGLO p: NF-YA6 - VP16 plants. These results suggest that the introduction of the TfGLO p: NF-YA6-VP16 induced TfPLE expression, resulting in the formation of staminoid petals and separation of them.